Bilgisayar destekli plastik kalıp tasarımı ve imalat aşamalarının incelenmesi - Özyiğit, Öznur (My University, 2005)
Plastics are nowadays important engineering materials due to their specific characteristics, such as corrosion resistance, resistance to chemicals, low density, easy of manufacture, etc. and have increasingly replaced metallic components in industrial applications. Injection molding is one of the important forming processes for plastic products. The surface finish quality of the plastic injection mold is an essential requirement due to its direct effects on the appearance of the plastic product. Finishing processes such as grinding, polishing, and lapping, are commonly used to improve the surface finish. The focus of this thesis is in the computer aided design and manufacturing steps of the plastic moulds. For instance The cooling system which plays an important role in the product quality. The function of the cooling system of a plastic injection mould is to provide thermal regulation in the injection moulding process. Proengineer program was used to analyze cooling system. Therefore temperature profile that changes with cooling time is predicted. Efficiency and quality can thus be estimated before the actual mold fabrication. A cam shaft which is used on electricall devices is designed and analyzed by Proengineering Software. It is compared some parameters which are number of mould eyes, location of cool canals, location hall rug etc. It is decided optimum dimensions of plastic moulding and manufactured by CNC Machines. Plastic moulding which is manufactured is tested and obtained samples. Also It is prepared workshop table which is shown steps of manufacturing plastic moulding. Plastikler son zamanlarda korozyona dirençleri, düşük yoğunluk, kolay imalat edilebilirlik vb. özelliklerinden dolayı endüstride metal malzemelerin yerine daha çok kullanılmaya başlanmıştır. Enjeksiyon kalıpları plastik ürünlerin şekillendirilmesinde çok önemlidir. Kalıpların yüzeylerinin kaliteli işlenmiş olması gerekir. Kalıp bitirme yüzeyleri için taşlama ve parlatma işlemleri uygulanır. Bu tezde plastik kalıpların bilgisayar destekli tasarımları ve imalat adımları üzerinde incelemelere ağırlık verildi. Ürünün kalitesine doğrudan etkisi olan soğutma sistemleri örnek olarak gösterilebilir. Plastik malzemenin boşluk içerisindeki ısısal dengesini düzenleyen fonksiyona sahiptir. Soğutma sisteminin analizinde Proengineer yazılımı kullanıldı. Sıcaklık profilinin değişimleri tahmin edildi. Kalıp imal edilmeden önce kalitesi ve güvenirliği test edildi. Elektriksel cihazlarda kullanılan bir kam milinin Proengineer yazılımı ile tasarımı ve analizi yapıldı. Kalıp göz sayısı, soğutma kanallarını yerleşimi ve yollukların yerleri kalıp teorik ve amprik teknolojik bilgiler kullanılarak karşılaştırıldı. CNC makinaları ile imalatı yapılan kalıbın boyutlarına karar verildi. Kalıptan numuneler alınarak test edildi. Ayrıca kalıp imalat aşamalarını adım adım gösteren bir duvar dolabı hazırlandı.
Keywords: Bilgisayar Destekli Tasarım